THE THE CORRELATION BETWEEN WRIST POSITION WHEN TYPING AND THE OCCURRENCE OF CTS (CARPAL TUNNEL SYNDROME) AMONG PT. X EMPLOYEES - Setiawan, Made Adhi Dharma; Winaya, I Made Niko; Muliarta, I Made (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT Employees who operate computer and are typing on keyboard everyday have higher risk of wrist pain because of non -ergonomic work position. This study was conducted to assess the relationship between wrist position when typing and risk level of CTS (Carpal Tunnel Syndrome) in employees of PT.X. This study is an analytical observational study with cross-sectional study design. The population in this study is the employee of PT.X. The sample consists of 66 people. The subjects are 30-50 years old men and women who have been working for more than a year. The tests used in this research are bivariate analysis Pearson Product Moment and univariate analysis. The result shows that 15 of 66 employees (22,7%) have good postures and 51 of 66 employees (77,3%) have bad work postures. 39 of 66 employees (59,1%) have risk of CTS and 27 of 66 employees (59,1%) do not have risk of CTS. The final result of Chi Square Test shows the significance of 0,000 (p<0,05). The result of the statistic tests shows that wrist position when typing has significant relationship with the risk of CTS (Carpal Tunnel Syndrome). Keywords : Wrist Position, Employees, Carpal tunnel syndrome.